Undertaking effective medication reviews. Issue 8 (August 2013) - Avery, Tony; Gookey, Gill; Spencer, Rachel; Knox, Richard; Marsden, Kate; Salema, Ndeshi
In the General Medical Council-funded PRACtICe study around half the prescribing and monitoring errors identified involved repeat prescriptions. This suggests a need to improve the effectiveness of medication reviews in order to ensure that any errors are detected and corrected. In this article we focus on identifying the elements of an effective medication review; providing examples of medication reviews, and identifying and tackling adherence issues. The article gives the reader opportunities to reflect upon different scenarios, and there are also suggestions for additional continuing professional development activities.